Common wealth : economics for a crowded planet - Sachs, Jeffrey. (Penguin Press, 2008)
Assessment of the environmental degradation, rapid population growth, and extreme poverty that threaten global peace and prosperity, with practical solutions based on a new economic paradigm for our crowded planet.